Maize Canopy Apparent Photosynthesis and 13C-Photosynthate Reallocation in Response to Different Density and N Rate Combinations - Wei, Shanshan; Wang, Xiangyu; Li, Guanghao; Jiang, Dong; Dong, Shuting (Frontiers in Plant Science, 2019)
The objective of this work was to analyze the responses of maize plants to combinations of various plant densities and nitrogen rates considering their canopy apparent photosynthesis (CAP) and assimilate redistribution characters by 13CO2 stable isotope tracing. In this study, maize plants were grown at various planting densities (6.75, 8.25, 9.75, and 11.25 pl m-2) and N application rates (0, 180, 270, 360, and 540 kg ha-1) during 2013–2015 in Shandong, China. The maize varieties Denghai618 and Denghai605 were used as the study materials. At the community level, grain yield (GY) was maximized at a density of 9.75 pl m-2 with a 270–360 kg ha-1 N rate during the 3 study years. The CAP and leaf area index (LAI) was both enhanced significantly by increased density and N rate, while the yield improvement was more associated with the increase in CAP. By contrast, excess N had inhibitory effects and decreased the GY consequently. Increased N supply weakened the decreased KNP and TKW caused by enhanced density mainly by decreasing the retention of 13C-photosynthates in the stem and promoting 13C-photosynthate reallocation to reproductive organs. The GY, biomass, CAP, LAI and 13C-photosynthate reallocation ratio to different organs all responded more intensively to density than N rate, though the response degree differed between varieties. Based on our results, greater CAP, higher use of reserves and more 13C-photosynthate distribution to ears are all vital for the further improvement of maize GY under different density and N rate combinations.